Analysis of User Satisfaction with the Hallo Palembang Website Using the UTAUT 2 Model - Aryawira Adhi Pradana (Institute of Information Technology and Social Science (IITSS), 2024)
Information systems have evolved alongside the rapid advancement of information technology and have been proven to play crucial roles in diverse activities. Hallo Palembang is an information platform managed by the Communication and Informatics Office of the City of Palembang. It is designed to provide comprehensive public services, including event listings, reporting centers, and citizen complaint management. However, an evaluation of its usage is essential to determine user satisfaction and to identify potential areas for improvement and feature enhancement. This study employs the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model to examine user intentions and behaviors toward the Hallo Palembang website. The research sample comprises residents of Palembang City who actively use or access the platform. The objective is to identify variables that significantly influence user acceptance. The results of this user-satisfaction analysis are expected to facilitate a more efficient understanding of the behavioral patterns and preferences of Hallo Palembang users.